Development of an Interactive Parenting E-Book as an Educational Tool for Parents in Fostering Early Childhood Character Development - Roudlotun Ni'mah; Endang Puspitasari; Anna Prasassty (Journal of Childhood Development, 2026)
The role of parents in early childhood character education is essential in shaping children's moral values, discipline, responsibility, and social behavior. However, the limited availability of practical and engaging parenting media has resulted in suboptimal parental involvement in children's character education. This study aimed to develop an interactive parenting e-book to enhance parents' roles in early childhood character education at Tarbiyatul Islam Kindergarten, Sokosari, Soko. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The research participants included 20 parents, 20 children aged 5–6 years, and 2 teachers from Group B classes. Data were collected through observation, interviews, questionnaires, and documentation. The results indicated that the interactive parenting e-book was categorized as highly feasible, with validation scores of 92% from material experts, 90% from media experts, and 94% from language experts. The implementation results also demonstrated an increase in parental involvement in children's character education, as reflected in the improvement of pretest and posttest scores from an average of 60.4% to 88.2%. Therefore, the interactive parenting e-book can be utilized as an effective and innovative digital educational medium to support parenting programs in early childhood education.